Possible pathways for low carbon transitions: Investigating the efforts of oil companies in CCUS technologies - Thanh Hue Truong; Bou-Wen Lin; Ching-Hua Lo; Ching-Pin Tung; Chia-Wei Chao (Energy Strategy Reviews, 2024)
Oil and gas industries within the energy sector are a significant contributor to carbon dioxide (CO2) emissions, a primary driver of climate change and global warming. However, research on their efforts to combat this issue remains limited. This study investigates climate initiatives by five major oil companies, emphasizing carbon capture, utilization, and storage (CCUS). Analyzing 98,730 patents from 2000 to 2022, the results show that they collectively registered 871 CCUS-related patents. ExxonMobil leads with 359, followed by Shell, though 70 % of its patents are inactive. The primary technical fields of these five companies include technologies developed to capture and dispose of CO2, and to utilize a bio-feedstock approach in the oil refining and petrochemical industry. Our findings reveal that all five companies have strategically integrated CCUS into their business operations, forming partnerships with third-party emitters as partners and customers, and implementing efforts to lower the carbon burden of existing assets. These findings are expected to help with strategic decision-making, guiding targeted investments, and paving the way for future research and development endeavors in the rapidly evolving CCUS domain.